Editorial: Operationalizing the nature futures framework to catalyze the development of nature-future scenarios - Shizuka Hashimoto; Jan J. Kuiper; Garry D. Peterson; Laura Pereira; Mekuria Argaw Denboba; Carolyn Lundquist (Sustainability Science, 2026)
Global biodiversity scenarios have long struggled to capture the diversity of ways people value and relate to nature, favoring instrumental, growth-oriented framings over relational and intrinsic perspectives. The Nature Futures Framework (NFF) was developed to address this gap, offering a pluralistic, target-seeking approach to imagining nature-positive futures. This Special Feature brings together contributions that advance the operationalization of the NFF across methods, geographies, and thematic domains—from visioning, narrative development and participatory co-creation to quantitative modeling and governance design. Drawing on these papers, we identify three cross-cutting lessons: the NFF functions best as a boundary object for negotiating plural values rather than a fixed typology; its operationalization depends on combining narratives, indicators, models, deliberation, and institutional design rather than any single method; and its next frontier lies in implementation, linking NFF-based scenarios to the policy instruments and governance institutions such as the Kunming-Montreal Global Biodiversity Framework. We highlight the NFF’s strengths in fostering value pluralism, expanding the scope of possible futures, and identifying trade-offs and synergies among competing priorities. However, we also acknowledge the following persistent challenges: translating qualitative, place-based values into quantitative models, preventing the standardization of relational values, and navigating the normative and political tensions involved in defining “desirable” futures. In closing, we outline a research agenda centered on developing pluralistic indicators, strengthening integrated social-ecological modeling, exploring alternative economic paradigms, and deepening inclusive co-production. As global biodiversity governance shifts toward implementation, we argue that the NFF is now well positioned to move from concept to practice.

Deep learning approach for genetic selection of stress response in the Amazon fish Colossoma macropomum - Celma G. Lemos; Baltasar F. Garcia; Marcelo S.S. Filho; Jairo R. Arango; Arno J. Butzge; Luciana Shiotsuki; Luiz Eduardo L. Freitas; Fabrício P. Rezende; Elisabeth C. Urbinati; Guilherme J.M. Rosa; Diogo T. Hashimoto (Aquaculture, 2025)

Catalyzing change: a literature review on the implementation of the Nature Futures Framework - Sana Okayasu; Jan J. Kuiper; Ghassan Halouani; HyeJin Kim; Brian W. Miller; América Paz Durán; Angelique Vermeer; Machteld Schoolenberg; Shizuka Hashimoto; Carolyn Lundquist (Sustainability Science, 2025)
The Nature Futures Framework (NFF), developed under the Intergovernmental Science–Policy Platform on Biodiversity and Ecosystem Services (IPBES), serves as a catalyst for advancing new scenarios and models focused on biodiversity and ecosystem services within the broader research community. In particular, the framework facilitates the development of scenarios and models that can help guide change processes toward desirable futures for nature and people. This paper assesses 31 studies that have engaged with the NFF since its introduction in 2020, aiming to identify which research areas have been addressed, and where development needs remain. The applications exhibit a large diversity in terms of locations, spatial scales, methods, outputs, and stakeholder involvement. The most common use of the framework has been in developing visions and scenarios. Nearly all studies engaged with diverse values of nature through the framework’s fundamental value perspectives: ‘ Nature for Society ’, ‘ Nature for Natur e’, and ‘ Nature as Culture / One with Nature ’. While the framework is generally perceived as useful, challenges remain in integrating the NFF across multiple scales and fully incorporating plural values, particularly in measuring relational aspects and avoiding Western-centric biases. Future research priorities include developing integrated, quantitative studies and exploring transformative pathways to enhance the framework's effectiveness in driving sustainable outcomes. Overall, the growing body of work using the NFF provides a strong foundation for distilling best practices, facilitating large-scale applications, and achieving the framework's objectives.

Association between maternal urinary cotinine concentrations during pregnancy and neonatal blood thyroid-stimulating hormone levels: The Japan environment and Children's study (JECS) - Keiko Yamasaki; Naw Awn J-P; Naomi Mitsuda; Masamitsu Eitoku; Nagamasa Maeda; Ryuhei Nagai; Hiroaki Hisakawa; Narufumi Suganuma; Michihiro Kamijima; Shin Yamazaki; Maki Fukami; Reiko Kishi; et al. (International Journal of Hygiene and Environmental Health, 2025)

OpenSBLI v3.0: High-fidelity multi-block transonic aerofoil CFD simulations using domain specific languages on GPUs - David J. Lusher; Andrea Sansica; Neil D. Sandham; Jianping Meng; Bálint Siklósi; Atsushi Hashimoto (Computer Physics Communications, 2025)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Hydrologic-geotechnical modelling of shallow landslide and flood hazards caused by heavy rainfall - Nilo Lemuel J. Dolojan; Shuji Moriguchi; Masakazu Hashimoto; Nguyen Xuan Tinh; Hitoshi Tanaka; Kenjiro Terada (Engineering Geology, 2023)

Bringing the Nature Futures Framework to life: creating a set of illustrative narratives of nature futures - América Paz Durán; Jan J. Kuiper; Ana Paula Dutra Aguiar; William W. L. Cheung; Mariteuw Chimère Diaw; Ghassen Halouani; Shizuka Hashimoto; Maria A. Gasalla; Garry D. Peterson; Machteld A. Schoolenberg; Rovshan Abbasov; Lilibeth A. Acosta; et al. (Sustainability Science, 2023)
To halt further destruction of the biosphere, most people and societies around the globe need to transform their relationships with nature. The internationally agreed vision under the Convention of Biological Diversity—Living in harmony with nature—is that “By 2050, biodiversity is valued, conserved, restored and wisely used, maintaining ecosystem services, sustaining a healthy planet and delivering benefits essential for all people”. In this context, there are a variety of debates between alternative perspectives on how to achieve this vision. Yet, scenarios and models that are able to explore these debates in the context of “living in harmony with nature” have not been widely developed. To address this gap, the Nature Futures Framework has been developed to catalyse the development of new scenarios and models that embrace a plurality of perspectives on desirable futures for nature and people. In this paper, members of the IPBES task force on scenarios and models provide an example of how the Nature Futures Framework can be implemented for the development of illustrative narratives representing a diversity of desirable nature futures: information that can be used to assess and develop scenarios and models whilst acknowledging the underpinning value perspectives on nature. Here, the term illustrative reflects the multiple ways in which desired nature futures can be captured by these narratives. In addition, to explore the interdependence between narratives, and therefore their potential to be translated into scenarios and models, the six narratives developed here were assessed around three areas of the transformative change debate, specifically, (1) land sparing vs. land sharing, (2) Half Earth vs. Whole Earth conservation, and (3) green growth vs. post-growth economic development. The paper concludes with an assessment of how the Nature Futures Framework could be used to assist in developing and articulating transformative pathways towards desirable nature futures.

Genome-wide association study of host resistance to the ectoparasite Ichthyophthirius multifiliis in the Amazon fish Colossoma macropomum - Lieschen V. G. Lira; Vito A. Mastrochirico-Filho; Natalia J. Mendes; Raquel B. Ariede; José M. Yáñez; Diogo T. Hashimoto (Molecular Biology Reports, 2023)

Influence of acute beetroot juice supplementation on cold-induced vasodilation and fingertip rewarming - Hitoshi Wakabayashi; Koji Sugiyama; Shinichi Suzuki; Yasuko Sakihama; Makoto Hashimoto; Martin J. Barwood (European Journal of Applied Physiology, 2022)

Gene-associated markers as a genomic and transcriptomic resource for a highly migratory and apex predator shark (Isurus oxyrinchus) - Rodrigo R. Domingues; Vito Antonio Mastrochirico-Filho; Natalia J. Mendes; Diogo T. Hashimoto; Rui Coelho; Agostinho Antunes; Fausto Foresti; Fernando F. Mendonça (Marine Biology, 2022)

Strategic roadmap to assess forest vulnerability under air pollution and climate change - Alessandra De Marco; Pierre Sicard; Zhaozhong Feng; Evgenios Agathokleous; Rocio Alonso; Valda Araminiene; Algirdas Augustatis; Ovidiu Badea; James C. Beasley; Cristina Branquinho; Viktor J. Bruckman; Alessio Collalti; et al. (Global Change Biology, 2022)
Although it is an integral part of global change, most of the research addressing the effects of climate change on forests have overlooked the role of environmental pollution. Similarly, most studies investigating the effects of air pollutants on forests have generally neglected the impacts of climate change. We review the current knowledge on combined air pollution and climate change effects on global forest ecosystems and identify several key research priorities as a roadmap for the future. Specifically, we recommend (1) the establishment of much denser array of monitoring sites, particularly in the South Hemisphere; (2) further integration of ground and satellite monitoring; (3) generation of flux‐based standards and critical levels taking into account the sensitivity of dominant forest tree species; (4) long‐term monitoring of N, S, P cycles and base cations deposition together at global scale; (5) intensification of experimental studies, addressing the combined effects of different abiotic factors on forests by assuring a better representation of taxonomic and functional diversity across the ~73,000 tree species on Earth; (6) more experimental focus on phenomics and genomics; (7) improved knowledge on key processes regulating the dynamics of radionuclides in forest systems; and (8) development of models integrating air pollution and climate change data from long‐term monitoring programs.

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Correction to: Mapping method of rainfall-induced landslide hazards by infiltration and slope stability analysis - Nilo Lemuel J. Dolojan; Shuji Moriguchi; Masakazu Hashimoto; Kenjiro Terada (Landslides, 2021)

Mapping method of rainfall-induced landslide hazards by infiltration and slope stability analysis - Nilo Lemuel J. Dolojan; Shuji Moriguchi; Masakazu Hashimoto; Kenjiro Terada (Landslides, 2021)

Fostering biocultural diversity in landscapes through place-based food networks: a “solution scan” of European and Japanese models - Tobias Plieninger; Ryo Kohsaka; Claudia Bieling; Shizuka Hashimoto; Chiho Kamiyama; Thanasis Kizos; Marianne Penker; Pia Kieninger; Brian J. Shaw; Giles Bruno Sioen; Yuki Yoshida; Osamu Saito (Sustainability Science, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.

Origin of B chromosomes in the genus Astyanax (Characiformes, Characidae) and the limits of chromosome painting - Duílio M. Z. de A. Silva; Sandro Natal Daniel; Juan Pedro M. Camacho; Ricardo Utsunomia; Francisco J. Ruiz-Ruano; Manolo Penitente; José Carlos Pansonato-Alves; Diogo Teruo Hashimoto; Claudio Oliveira; Fábio Porto-Foresti; Fausto Foresti (Molecular Genetics and Genomics, 2016)

Effects of the potential lithium-mimetic, ebselen, on brain neurochemistry: a magnetic resonance spectroscopy study at 7 tesla - Charles Masaki; Ann L. Sharpley; Beata R. Godlewska; Adam Berrington; Tasuku Hashimoto; Nisha Singh; Sridhar R. Vasudevan; Uzay E. Emir; Grant C. Churchill; Philip J. Cowen (Psychopharmacology, 2016)

Triassic–Jurassic granites on the Lord Howe Rise, northern Zealandia - N. Mortimer; R. E. Turnbull; J. M. Palin; A. J. Tulloch; N. Rollet; T. Hashimoto (Australian Journal of Earth Sciences, 2015)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

Comparative Protein Composition of the Brains of PACAP-Deficient Mice Using Mass Spectrometry-Based Proteomic Analysis - G. Maasz; Z. Pirger; D. Reglodi; D. Petrovics; J. Schmidt; P. Kiss; A. Rivnyak; H. Hashimoto; P. Avar; E. Jambor; A. Tamas; B. Gaszner; et al. (Journal of Molecular Neuroscience, 2014)

Examination of Calcium-Binding Protein Expression in the Inner Ear of Wild-Type, Heterozygous and Homozygous Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP)-Knockout Mice in Kanamycin-Induced Ototoxicity - A. Nemeth; K. Szabadfi; B. Fulop; D. Reglodi; P. Kiss; J. Farkas; B. Szalontai; R. Gabriel; H. Hashimoto; A. Tamas (Neurotoxicity Research, 2014)

A large hydrothermal reservoir beneath Taal Volcano (Philippines) revealed by magnetotelluric resistivity survey: 2D resistivity modeling - Y. Yamaya; P. K. B. Alanis; A. Takeuchi; J. M. Cordon; T. Mogi; T. Hashimoto; Y. Sasai; T. Nagao (Bulletin of Volcanology, 2013)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

The pigment stoichiometry in a chlorophyll a/c type photosynthetic antenna - Ritsuko Fujii; Mamiko Kita; Matsumi Doe; Yoshiro Iinuma; Naohiro Oka; Yuki Takaesu; Tomonori Taira; Masahiko Iha; Tadashi Mizoguchi; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2012)

Isolation and purification of the major photosynthetic antenna, fucoxanthin-Chl a/c protein, from cultured discoid germilings of the brown Alga, Cladosiphon okamuranus TOKIDA (Okinawa Mozuku) - Ritsuko Fujii; Mamiko Kita; Yoshiro Iinuma; Naohiro Oka; Yuki Takaesu; Tomonori Taira; Masahiko Iha; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2012)

Androgen Receptor Overexpression Is Neuroprotective in Experimental Stroke - Patricia Ayala; Masayoshi Uchida; Kozaburo Akiyoshi; Jian Cheng; Joel Hashimoto; Taiping Jia; Oline K. Ronnekleiv; Stephanie J. Murphy; Kristine M. Wiren; Patricia D. Hurn (Translational Stroke Research, 2011)

Ion microprobe (SHRIMP) U–Pb dating of Upper Cretaceous volcanics from the northern Lord Howe Rise, Tasman Sea - K. Higgins; T. Hashimoto; G. Fraser; N. Rollet; J. Colwell (Australian Journal of Earth Sciences, 2011)

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Proliferation of kuchijirosho causative agent in a fugu‐derived cell line - E Hashimoto; T Miyadai; M Ohtani; S‐I Kitamura; M‐J Oh (Journal of Fish Diseases, 2008)
Kuchijirosho is a fatal disease of commercially cultured fugu, Takifugu rubripes . The transmissible nature of kuchijirosho strongly suggests that an infectious pathogen is the causative agent. Because it is filtrable, the agent is thought to be a virus; however, it has not yet been identified. The lack of a permissive cell line for the putative kuchijirosho‐causing agent (KCA) has hindered research on the identification of this pathogen. We inoculated brain extract prepared from kuchijirosho‐affected fugu onto an established fugu cell line, fugu eye, and observed that cytopathic effect appeared 7 days after inoculation. Injection of the culture medium of infected fugu eye cells into fugu resulted in the onset of kuchijirosho, indicating that fugu eye cells are able to proliferate KCA. An infectious fraction separated by sodium iottalamate density gradient centrifugation showed a density of 1.15 g mL −1 equivalent to that of KCA derived from affected fugu brain. To determine whether the genome of KCA is RNA or DNA based, nucleotide synthesis inhibitors were applied to inoculated fugu eye cell line to influence the production of KCA. 5‐Fluorouracil but not IUdR showed a concentration‐dependent inhibition of KCA yield. These results suggest that KCA is an RNA virus.

Four-wave mixing signals from β-carotene and its n = 15 homologue - Mitsuru Sugisaki; Masazumi Fujiwara; Kazuhiro Yanagi; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2008)

Construction of hybrid photosynthetic units using peripheral and core antennae from two different species of photosynthetic bacteria: detection of the energy transfer from bacteriochlorophyll a in LH2 to bacteriochlorophyll b in LH1 - Ritsuko Fujii; Shozo Shimonaka; Naoko Uchida; Alastair T. Gardiner; Richard J. Cogdell; Mitsuru Sugisaki; Hideki Hashimoto (Photosynthesis Research, 2008)

Linear and nonlinear optical responses in bacteriochlorophyll a - Mitsuru Sugisaki; Ritsuko Fujii; Richard J. Cogdell; Hideki Hashimoto (Photosynthesis Research, 2008)

Electrostatic effect of surfactant molecules on bacteriochlorophyll a and carotenoid binding sites in the LH1 complex isolated from Rhodospirillum rubrum S1 probed by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Probing binding site of bacteriochlorophyll a and carotenoid in the reconstituted LH1 complex from Rhodospirillum rubrum S1 by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Nucleotide sequence analysis of seven Japanese isolates of Plantago asiatica mosaic virus (PlAMV): a unique potexvirus with significantly high genomic and biological variability within the species - K. Komatsu; Y. Yamaji; J. Ozeki; M. Hashimoto; S. Kagiwada; S. Takahashi; S. Namba (Archives of Virology, 2008)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genome sequence of a Japanese isolate of Radish mosaic virus: the first complete nucleotide sequence of a crucifer-infecting comovirus - K. Komatsu; M. Hashimoto; K. Maejima; J. Ozeki; S. Kagiwada; S. Takahashi; Y. Yamaji; S. Namba (Archives of Virology, 2007)

Clathrin is involved in organization of mitotic spindle and phragmoplast as well as in endocytosis in tobacco cell cultures - H. Tahara; E. Yokota; H. Igarashi; H. Orii; M. Yao; S. Sonobe; T. Hashimoto; P. J. Hussey; T. Shimmen (Protoplasma, 2007)

Involvement of Aquaporin-5 Water Channel in Osmoregulation in Parotid Secretory Granules - M. Matsuki; S. Hashimoto; M. Shimono; M. Murakami; J. Fujita-Yoshigaki; S. Furuyama; H. Sugiya (The Journal of Membrane Biology, 2005)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Purple Bacterial Light-harvesting Complexes: From Dreams to Structures - Richard J. Cogdell; Hideki Hashimoto; Alastair T. Gardiner (Photosynthesis Research, 2004)

Phylogenetic relationships of deep-sea mussels of the genus Bathymodiolus (Bivalvia: Mytilidae) - J.-I. Miyazaki; M. Shintaku; A. Kyuno; Y. Fujiwara; J. Hashimoto; H. Iwasaki (Marine Biology, 2004)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Fujikura K.; Hashimoto J. (Marine Biology, 2002)

Carotenoids and bacterial photosynthesis: The story so far... - Niall J. Fraser; Hideki Hashimoto; Richard J. Cogdell (Photosynthesis Research, 2001)

Retrolyc1 subfamilies defined by different U3 LTR regulatory regions in the Lycopersicon genus - P. Araujo; J. Casacuberta; A. Costa; R. Hashimoto; M.-A. Grandbastien; M.-A. Van Sluys (Molecular Genetics and Genomics, 2001)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific. I. Family Lamellibrachiidae - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Hashimoto J. (Marine Biology, 2001)

Structure of the infected cell protein 0 gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 2000)

Antibacterial characteristics of magnesium oxide powder - J. Sawai; H. Kojima; H. Igarashi; A. Hashimoto; S. Shoji; T. Sawaki; A. Hakoda; E. Kawada; T. Kokugan; M. Shimizu (World Journal of Microbiology and Biotechnology, 2000)

Dynamic changes in corticospinal excitability during motor imagery - Ritsuo Hashimoto; J. C. Rothwell (Experimental Brain Research, 1999)

Structure of the immediate early gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

Habitat Use and Ranging of Wild Bonobos (Pan paniscus) at Wamba - Chie Hashimoto; Yasuko Tashiro; Daiji Kimura; Tomoo Enomoto; Ellen J. Ingmanson; Gen'ichi Idani; Takeshi Furuichi (International Journal of Primatology, 1998)

Enhanced human tumor cell transplantability in a new congenic immunodeficient mouse; KSN-BNX - Y. Ishigaki; K. Yasuda; N. Hashimoto; H. Nikaido; O. Nikaido; J. -I. Hayakawa (Folia Microbiologica, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Molecular phylogeny of vestimentiferans collected around Japan, revealed by the nucleotide sequences of mitochondrial DNA - S. Kojima; R. Segawa; J. Hashimoto; S. Ohta (Marine Biology, 1997)

Modes of Seoul virus infections: persistency in newborn rats and transiency in adult rats - H. Kariwa; M. Kimura; S. Yoshizumi; J. Arikawa; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1996)

Identification of mutation sites of a temperature-sensitive mutant of HCMV DNA polymerase activity - S. Ihara; M. Takekoshi; N. Mori; S. Sakuma; J. Hashimoto; Y. Watanabe (Archives of Virology, 1994)

Antibody-dependent enhancement of hantavirus infection in macrophage cell lines - J. -S. Yao; H. Kariwa; I. Takashima; K. Yoshimatsu; J. Arikawa; N. Hashimoto (Archives of Virology, 1992)

Protective role of antigenic sites on the envelope protein of Hantaan virus defined by monoclonal antibodies - J. Arikawa; J. -S. Yao; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1992)

Epidemiological studies of hemorrhagic fever with renal syndrome (HFRS) related virus infection among urban rats in Hokkaido, Japan - J. Arikawa; I. Takashima; N. Hashimoto; K. Takahashi; K. Yagi; K. Hattori (Archives of Virology, 1986)

Cell fusion by haemorrhagic fever with renal syndrome (HFRS) viruses and its application for titration of virus infectivity and neutralizing antibody - J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1985)

Getah virus inAedes vexans nipponii andCulex tritaeniorhynchus: Vector susceptibility and ability to transmit - I. Takashima; N. Hashimoto; J. Arikawa; K. Matsumoto (Archives of Virology, 1983)